(untitled) (AmS-Skrifter, 2019)
Evolutionary biology and ethnographic analogy suggest that grandparenting has been critical to the development of human life history and may even explain modern human longevity. However, the roles and functions of grandparents have not previously been investigated in later prehistoric contexts. Ethnographic studies show that grandparents take on an extremely wide range of roles worldwide, whether this is teaching knowledge and skills, providing childcare, or even taking on parental roles and titles. In many cases, grandparents play a critical role in the support and socialization of children. Understanding the roles of grandparents thus has the potential to transform our understanding of prehistoric household and family structures. Through a case study of the Early Bronze Age Traisental in Austria, I explore potential methods for identification of grandparents in the past, and consider the effects of social formations on grandparenting.